Tingkat Kesadaran Multikultural Pada Guru SMA Lintas Generasi X, Milenial, dan Gen Z di Jakarta Selatan - Chandra Sagul Haratua (Journal of Social Research, 2025)
The development of the generation of teachers in the modern era of education raises questions about the extent to which generational differences affect professional abilities, including in terms of multicultural skills. This study aims to determine the difference in the level of multicultural skills in teachers across generations, namely Generation X, Millennials, and Z. This study uses a comparative quantitative approach with a descriptive analysis method. The research instrument is in the form of a multicultural skills questionnaire. The sample in this study is 120 teachers grouped into various generational groups. The results of the descriptive analysis showed that the average multicultural skill score in the generation X teacher group was 149.81, the Millennial generation teacher group was 148.36, and the generation Z teacher group was 148.07. Based on these results, it shows that multicultural skills in all generation groups are in the high category.